Development of a Mascot Design and Its Application in the Information Media of Dusun Semilir, Semarang Regency - Estu Utomo; Rahina Nugrahani Rahina Nugrahani; Muhammad Zaffwan Bin Idris Idris (Arty: Jurnal Seni Rupa, 2026)
This study aims to develop a comprehensive visual identity system for the Dusun Semilir tourist area in Semarang Regency to address issues of spatial navigation and branding inconsistencies. Using a research and development (R&D) methodology with a modified 3D model, specifically the Define, Design, and Develop phases, this study focuses on redesigning the existing beaver mascot, creating custom typography, and refining the tourist map. The results indicate that transforming the generic mascot into a 3D character with a strong personality enhances visitors’ emotional connection. Additionally, a custom typography inspired by the mascot’s anatomy was successfully created to ensure consistency across all promotional media. These elements were then fully integrated into the tourist map, designed with a systematic layout and visual hierarchy. Through this research, it was found that combining a 3D mascot, custom typography, and a tourist map into a unified system (bundling system) proved effective in addressing navigation challenges in large scale tourist areas. This integrated approach strengthens the destination’s professional image and enhances the quality of the visitor experience.